Automatic Promotion Policy and Academic Performance in Selected Primary Schools in Kabale Municipality - Drake, Kisheija (Kabale University, 2022)
The study examined the effect of automatic promotion on academic performance in government aided primary schools in Kabale municipality. Specifically, the study investigated the assessment mode for promotion in primary schools, assessed the academic performance indicators in primary schools; and established the relationship between automatic promotion and academic performance in government-aided primary schools in Kabale Municipality. The study used cross sectional survey design supported to collect and analyse both qualitative and quantitative data. A sample size of 252 respondents was selected from a population of 415 study units using purposive and simple random sampling. Descriptive statistics using frequencies, percentages, mean and standard deviation were used to describe the mode of assessment and academic performance performance indicators. Correlation was also used to test for the relationship between automatic promotion and academic performance, while regression was used to predict the effect of automatic promotion on academic performance. The study found that examinations are the key mode of assessing pupils for automatic promotion in Kabale Municipality; final exams and regular take home exercises improve pupils’ academic performance. The study concluded that automatic promotion negatively affects pupils’ academic performance. In recommendation, the Ministry of Education and Sports should consider training teachers in a range of assessment modes since automatic promotion heavily rests on teachers. At district level, there is need to motivate teachers through seminars, workshops, etc., to win their commitment to improving learners’ academic performance.